The British Experience in Preserving Digital Library Collections - Beagrie, Neil (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
The increasing amount of information being produced digitally is impacting on and changing forever the expectations of users in all spheres of life. Digital access has many advantages over paper-based access in terms of convenience and functionality. However there are challenges, not yet wholly resolved, associated with ensuring that the many and varied digital resources being created will continue to be accessible. The long-term preservation of research collections in digital form is therefore an issue of increasing concern to research libraries around the world. Preservation and access to this information is dependent on impermanent media and technologies and adapting or re-engineering existing organisational and legal frameworks.